Analisis Penerapan Sistem Pengendalian Internal dan Implikasinya Terhadap Temuan Audit: Studi Kasus Proyek Rehabilitasi Irigasi Wae Ces di Kabupaten Manggarai - Richardus Engel Tallo; Don Oscar Filius Sae; Alvonzo Rodriquez Watudhesi Toli; Oktavianus Hambur; Susana Purnamasari Baso (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
This study examines the implementation of the Government Internal Control System (Sistem Pengendalian Intern Pemerintah/SPIP) and its implications for audit findings in the Wae Ces Irrigation Rehabilitation Project, Manggarai Regency, East Nusa Tenggara. Despite the existence of a comprehensive regulatory framework governing internal control in the public sector, audit reports issued by the Audit Board of the Republic of Indonesia (BPK) continue to reveal recurring weaknesses in internal control and irregularities in regional infrastructure projects. This condition raises concerns regarding the effectiveness of SPIP in preventing deviations during project implementation. The purpose of this research is to analyze how internal control practices are applied in the Wae Ces project and to identify factors contributing to audit findings related to control weaknesses. This study employs a qualitative case study approach to capture an in-depth understanding of governance practices in a real operational context. Data were collected through in-depth interviews with BPK auditors, internal auditors (APIP), and regional financial management officials, complemented by document analysis of audit reports, project documentation, and relevant regulations. The findings indicate that audit issues primarily stem from limited human resource capacity, weak supervision mechanisms, inadequate separation of duties, and ineffective monitoring processes. These weaknesses reduce the effectiveness of SPIP and contribute directly to recurring audit findings, particularly in relation to compliance and physical project realization. The study highlights the importance of strengthening internal control systems to enhance accountability and prevent similar irregularities in regional infrastructure projects.